Emergency interventions for cardiogenic shock due to decompensated aortic stenosis: a systematic review and meta-analysis - Mauro Chiarito; Dario Bongiovanni; Evaldas Girdauskas; Bastian Wein; Eva Harmel; Tamer Owais; Stephanie Gladys Kühne; Andrea Patrignani; Sebastien Elvinger; Damyan Penev; Philip W Raake (Open Heart)
Background Cardiogenic shock (CS) induced by severe aortic stenosis (AS) is a life-threatening condition with high mortality. Despite advancements in emergency interventions, the optimal treatment approach remains uncertain.Aim This study aimed to systematically review and analyse the existing evidence on outcomes of emergency transcatheter aortic valve implantation (eTAVI) and emergency balloon aortic valvuloplasty (eBAV) in CS patients.Methods A systematic literature review and meta-analysis was performed. The primary endpoint was mortality at 30 days. Secondary endpoints were in-hospital mortality, 1-year mortality, bleeding, major vascular complications, myocardial infarction, stroke, incidence of pacemaker implantation, acute kidney injury and aortic regurgitation.Results Seventeen studies were included, totalling 2811 patients. The analysis revealed a 30-day mortality pooled estimated rate for eTAVI of 19% (CI 0.17 - 0.20) and for eBAV 39% (CI 0.32 - 0.46). In-hospital mortality pooled estimated rates were 11% for eTAVI (CI 0.06 - 0.18) and for eBAV 40% (CI 0.28 - 0.54). One-year mortality pooled estimated rates for eTAVI were 29% (CI 0.20 - 0.40) and for eBAV 67% (CI 0.58 - 0.74). Pooled estimated rates of any bleeding were 12% for eTAVI (CI 0.06 - 0.20) and 15% for eBAV (CI 0.10 - 0.21). The rate of major vascular complications for eTAVI was 8% (CI 0.07 - 0.10) and 3% for eBAV (CI 0.0 - 0.23).Conclusions This meta-analysis indicates that mortality in CS due to AS remains high despite emergency interventional treatment. These findings offer critical insights for clinical decision-making optimising patient care in this critically ill population.